Circular economy and environmental health in low- and middle-income countries - Wright, Caradee; Schwerdtle, Patricia (Globalization and health, 2019)
The circular economy framework for human production and consumption is an alternative to the traditional, linear concept of ‘take, make, and dispose’. Circular economy (CE) principles comprise of ‘design out waste and pollution’, ‘retain products and materials in use’, and ‘regenerate natural systems’. This commentary considers the risks and opportunities of the CE for low- and middle-income countries (LMICs) in the context of the Sustainable Development Goals (SDGs), acknowledging that LMICs must identify their own opportunities, while recognising the potential positive and negative environmental health impacts.
Gesehen am 24.01.2020